A Companion to Political Institutions in Poland, 1944-1989 - Jabłonowski, Marek, (Brill's Companions to the Slavic World ;, 2025)
This book presents to researchers and advanced students the essential knowledge about Polish political institutions when the country was a socialist "people's democracy" between 1944 and 1989. The focus is on organized and individual political actors, state bodies, parties, and socio-political movements. There are also chapters on the formalized legal framework that defined the forms of possible political activity and the specific political goals connected to them. The book brings together valuable material that has so far remained outside the mainstream of research and will contribute, especially among the researchers of English-speaking countries, to a better understanding of the latest history of Poland.